2001
DOI: 10.1034/j.1398-9995.2001.056005412.x
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilia, interleukin‐5, and tumour necrosis factor‐alpha in asthmatic children

Abstract: Serum levels of TNF-alpha and IL-5 were not related to peripheral eosinophilia and asthma severity in these children but were related to their own cellular production ex vivo. This study confirms that eosinophilia is the index of inflammation that is most closely related to the clinical severity of childhood asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…On the other hand, non-significant decrease was observed in serum IL-5 after 2 months of treatment with inhaled corticosteroids. This is in agreement with other reports [10,24] .They reported non-significant reduction of IL-5 after treatment with inhaled corticosteroids. However, this reported decrease of IL-5 may be related to the inhibitory role of inhaled corticosteroids as an anti-inflammatory drug on Th2 cells with subsequent suppression of IL-4 and IL-5 production [25].…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, non-significant decrease was observed in serum IL-5 after 2 months of treatment with inhaled corticosteroids. This is in agreement with other reports [10,24] .They reported non-significant reduction of IL-5 after treatment with inhaled corticosteroids. However, this reported decrease of IL-5 may be related to the inhibitory role of inhaled corticosteroids as an anti-inflammatory drug on Th2 cells with subsequent suppression of IL-4 and IL-5 production [25].…”
Section: Discussionsupporting
confidence: 83%
“…To learn whether IL-5 stimulates static adhesion to the soluble VCAM-1 splice forms, EOS were incubated with IL-5 and studied in cell adhesion assays. EOS incubated with 50 pg/ml IL-5, a concentration within the physiological range measured in the serum of human asthmatics (42)(43)(44), exhibited an ϳ1.5-fold enhancement in maximum adhesion to both 6d-VCAM-1 ( Fig. 2A) and 7d-VCAM-1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The loop between ␤ strands C and D in the first immunoglobulin (Ig)-like module is accessible on the protein surface and contains the core integrin-recognition sequence Ile 39 -Asp-Ser-Pro-Leu 43 (IDSPL) (11)(12)(13)(14)(15). A second IDSPL site is present in the CD loop in module 4 (12,14).…”
mentioning
confidence: 99%
“…A variety of studies [49][50][51][52][53][54][55][56][57] analyzed cytokine levels in body fluids [serum, sputum, BAL fluid (BALF) or all] from patients with asthma compared with healthy or disease-control individuals. The majority of these studies found that Th2-associated cytokines were elevated in body fluids from asthmatics compared with control individuals.…”
Section: Cytokines and Chemokinesmentioning
confidence: 99%